Տնտեսական համակարգերի նույնականացման շուրջ - Գալստյան Գագիկ (Bulletin of Yerevan University G: Economics, 2017)
Historical development of mankind is divided into certain periods. Yet in the economic science, there is no accepted and unified approach concerning the periodization of economic growth and development. In the present article, a comparison of the approaches to such divisions is presented with the aim of more exact diagnostics of the post-socialistic economic structures.